Teaching Arabic in the Dormitory of Maâhad Jamiâi of State Islamic University in Bandung: Toward a Total Immersion - Abdurahman, Maman; Rahman, Rahman; SaÃ¢Â€Â™diah, Ely (EDUCARE, 2018)
ABSTRACT: Arabic is indispensably necessary, especially in the Muslim-majority in Indonesia. However, it takes a lot of time to acquire Arabic, since there are various linguistic branches to learn for anyone who wishes to fluently understand it. On the top of that, Arabic has different characteristics from those of the Indonesian language. The present study was based on the results of a preliminary study that show a significant lack of Arabic teaching innovation, when compared with the teaching of other foreign languages, especially English. The purpose was to figure out the concept of Arabic teaching in the âMaâhad Jamiâiâ in terms of its objective, process, evaluation, issues, and challenges. To this end, an embedded case study was carried out. The data sources included informants, teaching activities, and documents. The data were analyzed using data source triangulation and an interactive model of method triangulation. The results show that the objective of Arabic teaching was to equip students with Arabic knowledge and skills in order for them to be able to keep up with the lesson and practice Arabic in university classrooms; the teaching process was theory and practice-oriented to create a conducive language learning environment; the evaluation was conducted through written and performance tests during the placement test, midterm test, and final test; and the teaching challenges lay in the psychological, educational, and social aspects. It is recommended that further studies deal with studentsâ interactions, second language acquisition, interference problem, and teaching components, specifically in the context of language dormitory.KEY WORDS:Â  Second Language Acquisition; âMaâhad Jamiâiâ Dormitory; Arabic Teaching Innovation; Students of Islamic State University; Total Immersion.Â Â About the Authors: Prof. Dr. Maman Abdurahman, Prof. Dr. Rahman, and Dr. Ely Saâdiah are the Lecturers at the Faculty of Language and Literature Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. For academic interests, corresponding author is: mamanabdurrahman@upi.eduSuggested Citation: Abdurahman, Maman, Rahman & Ely Saâdiah. (2018). âTeaching Arabic in the Dormitory of Maâhad Jamiâi of State Islamic University in Bandung: Toward a Total Immersionâ in EDUCARE: International Journal for Educational Studies, Volume 10(2), February, pp.75-86. Bandung, Indonesia and BS Begawan, Brunei Darussalam: Minda Masagi Press owned by ASPENSI and BRIMAN Institute, ISSN 1979-7877. Article Timeline: Accepted (November 16, 2017); Revised (January 5, 2018); and Published (February 28, 2018).